Preliminary study: paired clownfish (Amphiprion sp.) spawning pattern in indoor rearing system. (January 2020) - Sahusilawane, H A; Junior, M Z; Suprayudi, M A; Soelistyowati, D T; Tumbelaka, L I T A; Effendi, I
Abstract: Amphiprion sp. is known as the most popular tropical marine ornamental fish with unique colours and sequential hermaphroditic, social hierarchy and monogamous characteristics. Information on the spawning pattern of clownfish is very important. The purpose of this study was to evaluate the spawning patterns of Amphiprion sp. in indoor rearing system. Observations of spawning patterns were conducted for 14 days in paired of clownfish reared in aquarium sized 40×40×30 cm 3 with running water system. The results showed that maturation process in female started with the appearance of swollen abdomen and extended oviduct from the genital hole of female, then parent pair fish together cleaned the egg laying area, and spawned at 13.00-16.00. Spawning occurred on the fourth day to the seventh. The eggs were incubated for one week. During the incubation period, egg colour changed from orange on the first day to silver eye on seventh day, and the eggs hatched at 18.00-20.00 on eighth day. The spawning pattern of clownfish in indoor system is highly determined by time and environmental conditions.